Animistic design: how to reimagine digital interaction between the human and the nonhuman. Issue 1 (2nd January 2016) - Marenko, Betti; van Allen, Philip
ABSTRACT: This article puts forward the notion of animistic design as an uncertainty-driven strategy to reimagine human–machine interaction as a milieu of human and nonhuman. Animistic design is suggested as capable of fostering affects, sensibilities and thoughts that capitalize on the uncertain, the unpredictable and the nonlinear, and their capacity to trigger creative pathways. Informed by post-human philosophies, theories of mediation and materiality, as well as by affect, agency and aesthesia, animistic design eschews the anthropomorphic and the cute playfulness often associated with animism. Instead, it proposes a practical–theoretical framework to articulate the nexus of digital innovation, interaction design practices, technical materialities and affective responses already emerging in the digital cohabitation of the human and the nonhuman. Using a 'research through making' approach, the article describes in detail a series of animistic design experiments and prototyping methods that explore ways of rethinking interaction as an open-ended and creative enterprise. Animistic design offers an investigative strategy that exploits degrees of collaboratively curated uncertainty and unpredictability to imagine forms of digital interaction, and to engender creative human–nonhuman relationships within a given digital milieu.